Proteomic Analysis of Horseweed (Conyza canadensis) Subjected to Caprylic Acid Stress. Issue 9 (18th April 2019) - Li, Zuren; Kuang, Wei; Liu, Yongbo; Peng, Di; Bai, Lianyang
Abstract: Caprylic acid (CAP) is anticipated to be a potential biocontrol herbicide in the control of weeds, however the molecular mechanism of how CAP affects weeds is poorly understood. Here, the physiological and biochemical (protein‐level) changes in horseweed ( Conyza canadensis L.) are studied under CAP treatment, with infrared gas analyzer and label‐free quantitative proteomics methods. In total, 112 differentially‐accumulated proteins (DAPs) (>1.5 fold change, p < 0.05) are present between treated horseweed and control samples, with 46 up‐regulated and 66 down‐regulated proteins. These DAPs are involved in 28 biochemical pathways, including photosynthesis pathways. In particular, six photosynthesis proteins show significant abundance changes in the CAP‐treated horseweed. The qRT‐PCR results confirm three of the six genes involved in photosynthesis. Moreover, by measuring photosynthesis characteristics, CAP was shown to decrease photosynthetic rate, stomatal conductance, intercellular CO2 concentration, and the transpiration rate of horseweed. These results suggest that photosystem I is one of the main biological processes involved in the response of horseweed to CAP.